2022
DOI: 10.1002/pon.6059
|View full text |Cite
|
Sign up to set email alerts
|

mHealth program for patients with advanced cancer receiving treatment in a public health hospital in Brazil

Abstract: Objective: Previous studies have suggested the benefit of routine screening for biopsychosocial symptoms among patients with cancer. In recognition of the lack of data from low-and middle-income countries, this study sought to test and determine the effect of a mHealth program to screen biopsychological symptoms among patients with advanced breast or gynecological cancer.Methods: This was a quasi-experimental pre-post study conducted in a public hospital located in central western Brazil. Patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Ultimately, out of 35,541 documents, we included 244 (0.69%) documents (n=234, 95.9% scientific articles; n=6, 2.5% organizational reports; n=2, 0.8% health technology assessment frameworks [although the included literature covered additional frameworks]; and n=2, 0.8% web pages) in this review ( Figure 1 ). Out of 244 documents, our final sample comprised 60 (24.6%) literature reviews [ 19 , 40 - 98 ]; 49 (20.1%) viewpoints, commentaries, and editorials [ 11 , 13 , 17 , 99 - 144 ]; 43 (17.6%) cross-sectional studies [ 83 , 145 - 186 ]; 39 (16%) qualitative research articles [ 1 , 15 , 187 - 223 ]; 13 (5.3%) case reports [ 4 , 5 , 12 , 224 - 233 ]; 11 (4.5%) longitudinal studies [ 234 - 244 ]; 9 (3.7%) mixed methods studies [ 245 - 253 ]; 5 (2%) economic evaluations [ 254 - 258 ]; 5 (2%) randomized controlled trials [ 259 - 263 ]; 4 (1.6%) policy documents [ 264 - 267 ]; 3 (1.2%) preference studies [ 268 - 270 ]; 2 (0.8%) websites [ 271 , 272 ]; and 1 (0.4%) book chapter [ 273 ]. Of the 244 included studies, 23 (9.4%) were published before 2014 [ 41 , 66 , 71 , 96 , 98 , 116 , 122 , 124 - 126 , 129 , 130 , 132 , 158 , 163 , 167 , 171 , 192 , 211 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, out of 35,541 documents, we included 244 (0.69%) documents (n=234, 95.9% scientific articles; n=6, 2.5% organizational reports; n=2, 0.8% health technology assessment frameworks [although the included literature covered additional frameworks]; and n=2, 0.8% web pages) in this review ( Figure 1 ). Out of 244 documents, our final sample comprised 60 (24.6%) literature reviews [ 19 , 40 - 98 ]; 49 (20.1%) viewpoints, commentaries, and editorials [ 11 , 13 , 17 , 99 - 144 ]; 43 (17.6%) cross-sectional studies [ 83 , 145 - 186 ]; 39 (16%) qualitative research articles [ 1 , 15 , 187 - 223 ]; 13 (5.3%) case reports [ 4 , 5 , 12 , 224 - 233 ]; 11 (4.5%) longitudinal studies [ 234 - 244 ]; 9 (3.7%) mixed methods studies [ 245 - 253 ]; 5 (2%) economic evaluations [ 254 - 258 ]; 5 (2%) randomized controlled trials [ 259 - 263 ]; 4 (1.6%) policy documents [ 264 - 267 ]; 3 (1.2%) preference studies [ 268 - 270 ]; 2 (0.8%) websites [ 271 , 272 ]; and 1 (0.4%) book chapter [ 273 ]. Of the 244 included studies, 23 (9.4%) were published before 2014 [ 41 , 66 , 71 , 96 , 98 , 116 , 122 , 124 - 126 , 129 , 130 , 132 , 158 , 163 , 167 , 171 , 192 , 211 , …”
Section: Resultsmentioning
confidence: 99%
“…The mapped literature highlighted the multidimensionality and versatility of digital therapeutics by showcasing their relative advantages compared with their competitors. At the patient level, the most reported relative advantages were improvements in health outcomes and shortened disease duration through novel health care options, faster diagnoses, decrease in adverse medical events, and improved monitoring of clinical and patient-reported outcome measures [ 11 , 17 , 41 , 43 , 45 , 47 - 49 , 53 , 60 , 61 , 69 , 71 , 74 , 80 , 81 , 88 , 92 , 94 , 95 , 100 , 102 , 105 , 124 , 128 , 130 , 132 , 133 , 135 , 137 , 138 , 146 , 153 , 163 , 172 , 173 , 179 , 189 , 202 , 207 , 218 , 224 , 226 , 228 , 229 , 231 , 232 , 234 , 239 - 242 , 244 , 246 , 248 , 257 , 260 , 262 , 263 , 265 , 266 , 270 , 275 ], a...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have provided a step‐by‐step guide to the cultural adaptation process for cancer‐related interventions. Five studies focus on country specific issues within Kenya, 24 Ghana, 25 Uganda, 26 Indonesia 27 and Brazil 28 . All link together to highlight a common thread that psychosocial care is developing in LMICs but remains in need of improved access to resources.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
“…Five studies focus on country specific issues within Kenya, 24 Ghana, 25 Uganda, 26 Indonesia 27 and Brazil. 28 All link together to highlight a common thread that psychosocial care is developing in LMICs but remains in need of improved access to resources. The research reported within this Special Issue accentuates that implementation strategies can be developed through multi‐disciplinary and multi‐national collaboration.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%